MEMPROGRAMKAN PENGENALAN BANK SYARIAH PADA DESA CIJUJUNG, KECAMATAN CIBUNGBULANG, KABUPATEN BOGOR - Thantawi, Tubagus Rifqy; Anwar, Miftakhul; Sundari, Deoh (Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah: Program Studi Perbankan Syariah., 2024)
This community service aims to Program the Introduction of Sharia Banks in the Digital Era. The subject of this community service is the people of Cijujung Village, Cibungbulang District, Bogor Regency, West Java Province. In this community service, activities are carried out based on the presentation socialization method. The result of this community service is that the people of Cijujung Village do not have a good enough literacy of Sharia Bank knowledge. So that this socialization is very beneficial for the local community and opens new insights on the importance of Sharia Banks. With this community service, it can be concluded that the people of Cijujung Village can openly understand the importance of using Sharia Banks which must be the main point in halal life as a Muslim community